Effects of Neuromuscular Fatigue on Eccentric Strength and Electromechanical Delay of the Knee Flexors: The Role of Training Status - El-Ashker, Said; Chaabene, Helmi; Prieske, Olaf; Abdelkafy, Ashraf; Ahmed, Mohamed A.; Muaidi, Qassim I.; Granacher, Urs (Frontiers in Physiology, 2019)
Purpose: To examine the effects of fatiguing isometric contractions on maximal eccentric strength and electromechanical delay (EMD) of the knee flexors in healthy young adults of different training status. Methods: Seventy-five male participants (27.7 ± 5.0 years) were enrolled in this study and allocated to three experimental groups according to their training status: athletes (ATH, n=25), physically-active adults (ACT, n=25), and sedentary participants (SED, n=25). The fatigue protocol comprised intermittent isometric knee flexions (6-s contraction, 4-s rest) at 60% of the maximum voluntary contraction until failure. Pre- and post-fatigue, maximal eccentric knee flexor strength and EMDs of the biceps femoris, semimembranosus, and semitendinosus muscles were assessed during maximal eccentric knee flexor actions at 60, 180, and 300 °/s angular velocity. An analysis of covariance was computed with baseline (unfatigued) data included as a covariate. Results: Significant and large-sized main effects of group (p≤0.017, 0.87≤d≤3.69) and/or angular velocity (p<0.001, d=1.81) were observed. Post-hoc tests indicated that regardless of angular velocity maximal eccentric knee flexor strength was lower and EMD was longer in SED compared with ATH and ACT (p≤0.025, 0.76≤d≤1.82) and in ACT compared with ATH (p=≤0.025, 0.76≤d≤1.82). Additionally, EMD at post-test was significantly longer at 300°/s compared with 60°/s and 180°/s (p<0.001, 2.95≤d≤4.64) and at 180°/s compared with 60°/s (p<0.001, d=2.56), irrespective of training status. Conclusion: The main outcomes revealed significantly higher maximal eccentric strength and shorter eccentric EMDs of knee flexors in individuals with higher training status (i.e., athletes) following fatiguing exercises. Therefore, higher training status is associated with better neuromuscular functioning (i.e., strength, EMD) of the hamstring muscles in fatigued condition. Future longitudinal studies are needed to substantiate the clinical relevance of these findings.